PELAKSANAAN PELAYANAN PUBLIK BIDANG ADMINISTRASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK DI UNIVERSITAS RIAU TAHUN 2019-2020 - Siti Fatimah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Service activities are the process of fulfilling service needs in accordance with the laws and regulations for every citizen. Public services are very important, becoming something that can also be a benchmark for a developing or developed country. If public services in a country are good, then that country will surely develop soon, or even be advanced. As a profession, public service is based on the principles of professionalism and ethics such as accountability, effectiveness, efficiency, integrity, neutrality, and fairness for all service recipients. The formulation of the problem in this study is how the implementation of public services in the field of education at the Faculty of Social and Political Sciences, University of Riau in 2019-2020 and what are the factors that hinder the implementation of public services in the field of education at the Faculty of Social and Political Sciences, University of Riau in 2019-2020. The purpose of this study was to determine the implementation of public services in the field of education at the Faculty of Social and Political Sciences, University of Riau in 2019- 2020 and to determine the inhibiting factors for the implementation of public services in the field of education at the Faculty of Social and Political Sciences, University of Riau in 2019-2020. This research is based on indicators that become benchmarks in determining the quality of public services from Lenvine. The research method used is descriptive method with a qualitative approach. According to the author's analysis, the results of the study indicate that the implementation of public services in the field of education at the Faculty of Social and Political Sciences, Riau University is still low, because there are still problems regarding how the public service process is carried out. self. Factors supporting services have not been implemented properly, regarding operating hours the level of compliance is still low, there are still frequent inaccuracies in the service process and the lack of information provided to students in several majors. And civil servants in the field of administration, including leaders who are often not in the office. Bureau employees must increase their commitment and consistency in providing services so that the public service process in the field of administration runs well, and also the academic community must improve the quality of services with adequate facilities and infrastructure. Keywords: public service in education, professional, accountability, efficient